A bridge-like polymer synthesized by tandem metathesis cyclopolymerization and acyclic diene metathesis polymerization. Issue 7 (7th November 2014) - Song, Wei; Han, Huijing; Wu, Jianhua; Xie, Meiran
Abstract : A novel bridge-like polymer with excellent thermal stability, an ordered ladder-like structure, and a fence-like ribbon morphology was synthesized by tandem metathesis cyclopolymerization and acyclic diene metathesis polymerization. Abstract : A facile synthesis of a novel bridge-like polymer was accomplished by the combined procedures of metathesis cyclopolymerization (MCP) and acyclic diene metathesis (ADMET) polymerization. A telechelic double-stranded polyacetylene (PA) with two terminal alkenyl groups was firstly prepared through the third generation Grubbs' catalyst-mediated chain terminating MCP of bis(1, 6-heptadiyne), containing a perylene bisimide (PBI) segment, in the presence of 1, 4-bis(10-undecenyloxy)- cis -2-butene. A symmetrical triolefinic ether acted as the functional terminating agent, and was then utilized as the macromonomer in subsequent ADMET polymerization to yield the resultant bridge-like polymer, consisting of the nonconjugated polyolefin backbone and the separated pier-like double-stranded PA. The molecular weight of the product increased (25.2–122.4 kDa) as the reaction time was prolonged, and there was a relatively broad polydispersity index (PDI = 1.41–1.75). The bridge-like polymer can assemble into an ordered ladder-like architecture and a fence-like ribbon morphology, and displays excellent thermal stability, with a T d of above 300 °C and a high T g between 175 and 189 °C, which is important for applications in devices.